Projektowa rachunkowość zarządcza - Łada, Monika (Project Management Accounting, 2005)
The paper is focused on the framework of project management accounting system. In the literature on the subject the growing interest to this approach is observed. Based on the literature review the characteristics and application of project management accounting methods and techniques were outlined. The scope of the application of this concept in the practice was illustrated with the results of pilot studies conducted in 10 Polish project-oriented enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 232-240